(untitled) (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
The article deals with the importance of phrases in Modern English. The definition of the term is given and the differences between the phrases and sentences are clarified. The functions of the phrases are analyzed in the article as well.